Studi Literatur Penggunaan Minyak Atsiri Di Indonesia Untuk Mengatasi Gangguan Tidur - Kambira, Pretty Falena Atmanda; Lapian, Kristin Fransiska (Jurnal Locus Penelitian dan Pengabdian, 2025)
Sleep disorders are a health problem that is often experienced by various population groups, especially the elderly, infants, as well as pregnant and post-natal women. Aromatherapy with essential oils is one of the non-pharmacological approaches that is increasingly used because it is considered safer and more acceptable. Objective: This study aims to systematically review studies in Indonesia that evaluate the effectiveness of aromatherapy using essential oils on sleep quality. Method: The literature search was conducted using the Google Scholar search engine with the help of the Publish or Perish application. Keywords related to "aromatherapy", "essential oils", and "sleep disorders" are used to find suitable articles. Inclusion criteria include studies with essential oil interventions through inhalation or massage involving the population in Indonesia and containing sleep quality data as an output. Results: Twelve articles met the inclusion criteria. Most studies used lavender oil and showed a significant improvement in sleep quality. Some studies have also evaluated essential oils from local plants such as sandalwood, lynae, jasmine, and rose, which show positive results although their numbers are still limited. The duration of the intervention varied between one day and two months. The route of administration is generally through inhalation and massage, with no reports of serious side effects. Conclusion: Aromatherapy with essential oils, including from the local flora of Indonesia, has the potential to be an effective and safe non-pharmacological alternative to improve sleep quality. Further research is needed to strengthen scientific evidence, determine the optimal duration and dosage, and develop the economic potential of local resource-based essential oils.